Fork & Knife Corner / Mohamad Shakir Eddy Warman ... [et al.] - Eddy Warman, Mohamad Shakir; Ismail, Ahmad Hakimi; Saimi, Mohd Sazali; ismail, Amy Rizuanie; Zulkefli, Mas Idayu (Faculty of Hotel and Tourism Management, 2006)
We have decided to open a food business specializing in western food at Dataran Cendikia in University Technology Mara, Shah Alam. We choose the place as our location for business because of the strategic place that is located in the middle of colleges and faculties. The area is near colleges of Mawar, Melati and Anggerik. It is also near to the Faculty Of Engineering, Business, Information Study, Pharmacy and Law.